Konsep Makanan Halalan Thayyibah Dalam Perspektif Tafsir Al-Misbah: QS. Al-Baqarah 168 - Siregar, Fauziah Hanum; Harahap, Indra; Ashani, Sholahuddin (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
The study of the concept of halal thayyibah has become increasingly urgent in the modern era, when consumer lifestyles and food globalization pose challenges to the integrity of the ethical values ​​of Muslim consumption. The phenomenon of shifting meanings of halal, which are often reduced only to the legal aspects of fiqhiyah, encourages the need to re-examine the moral and spiritual dimensions of the teachings of the Quran. This study aims to analyze M. Quraish Shihab’s interpretation of QS. Al-Baqarah: 168 as stated in the Tafsir Al-Mishbah, to reveal the conceptual construction of halal thayyibah food that is complete between legal, ethical, and spiritual aspects. This study uses a qualitative approach with a thematic interpretation method (mauḍūʻī) based on textual analysis, which traces the network of lexical meanings, the context of the revelation of the verses, and the interpretive reasoning used by Quraish Shihab. The results show that linguistically, the terms halal and thayyib contain complementary dimensions between legal validity and substantial goodness that include aspects of health, hygiene, and social welfare. Contextually, Quraish Shihab interprets the verse as a universal call for humans to maintain the sanctity of consumption sources and consumer behavior that aligns with the values ​​of piety. The ethical and spiritual dimensions in this interpretation emphasize the balance between fulfilling physical needs and moral responsibility towards the environment and social justice. The implication is that the concept of halalan thayyibah functions not only as a legal norm but also as a principle of contemporary consumption ethics that guides Muslims to internalize ecological, social, and spiritual awareness in consumption activities. Thus, this research contributes to strengthening the paradigm of modern thematic interpretation that places the value of halalan thayyibah as an integral foundation for a comprehensive Islamic consumption ethic.